Captain Underpants and the big, bad battle of the Bionic Booger Boy, part 1 : the night of the nasty nostril nuggets : the sixth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2003)
A snotty situation ensues when Melvin Sneedley, an academically gifted student, turns into the Bionic Booger Boy and must be stopped by George, Harold, and Captain Underpants. By flipping the pages, the reader may view animated illustrations.
710
850
Accelerated Reader AR
Keywords: School principals -- Juvenile fiction; Schools -- Juvenile fiction; Heroes -- Juvenile fiction; Cartoons and comics -- Juvenile fiction; Humorous stories